Effects of remote work through the lens of self-determination theory - Honkanen, Arnold (My University, 2024)
Remote work is a significant phenomenon of the working world. The global COVID-19 pandemic has brought this phenomenon into the limelight as a ‘new normal’ for international organizations and employees alike. The ongoing technological development fuels this rapidly changing phenomenon which sets a new precedent for how work can be performed. This is a significant trend especially in the field of international business, with remote work being found to be a significant factor in how organizations are structured and how their culture is formed in a post-COVID world. This thesis is aimed to explore the effects of remote work in individuals who work in international business organizations as either full-time or hybrid remote workers via the perspective of self-determination theory. These three components of self-determination theory include autonomy, competence, and relatedness. The literature review of this study is focused on delving into the history and previous research of remote work and exploring and comparing other significant motivational theories to SDT. The empirical section of this study is based on in-depth individual interviews of remote work professionals. These findings are then reflected upon the perspective of managerial implications, seeking to answer what international business management can learn from this. The results of this study highlight remote workers as both autonomous, intrinsically motivated and competent workers of their respective fields. The great benefits of remote work are highlighted in increased flexibility, improved quality of leisure time and economic benefits to both organization and individual. A lack of social connectivity, especially in the form of informal connections, drives a wedge between individuals and organizations, causing difficulties in establishing company culture or making remote workers’ work feel less meaningful in a social context. Remote workers’ productivity compared to their in-office counterparts is found to either increase or stay the same based on the results of this study. Something this research adds to in the field of previous research on remote work is by highlighting the importance of the practical benefits of remote work and how they facilitate the benefits that have also been noted in previous research. This study delves deeper into the how and why remote work has the effects that it does on individuals. The managerial implications of this study highlight the need to further empower the remote workers’ autonomy and freedom while also calling organizations to take a brave step forward in implementing solutions that do not only mimic communication in a physical setting in an attempt to do damage control, but rise to equal standing with it by employing the use of, for example, co-working spaces or virtual or augmented reality.

Etätyö on kasvava ja muuttuva ilmiö työelämässä. Maailmanlaajuinen COVID-19-pandemia on vakiinnattunut etätyön asemaa ”uutena normaalina” työelämässä. Nopeasti kehittyvät uudet teknologiset innovaatiot luovat jatkuvasti erilaisia joustavia tapoja teettää ja tehdä työtä. Kansainvälisen liiketoiminnan saralla tämä muutos on merkittävä, ja COVID:in jälkeisessä maailmassa etätyö on noussut merkittäväksi organisaatiorakenteita ja -kulttuuria muovaavaksi tekijäksi. Tässä opinnäytetyössä tutkitaan etätyön vaikutuksia kansainvälisten yritysten työntekijöihin, jotka tekevät etätyötä joko koko- tai osa-aikaisesti. Tutkimus toteutetaan käyttäen itseohjautuvuusteoriaa tarkastelunäkökulmana. Itseohjautuvuusteorian kolme päätekijää ovat autonomia, kompetenssi ja yhteenkuuluvuuden tunne. Tämän tutkimuksen kirjallisuuskatsaus keskittyy syventymään etätyön historiaan ja aiempaan tutkimukseen etätyöstä sekä esittelemään itseohjautuvuusteorian lisäksi muita merkittäviä motivaatioteorioita, joita tutkimuksessa voitaisiin käyttää itseohjautuvuusteorian sijasta. Opinnäytteen empiirisessä osassa kootaan laadullinen aineisto syvällisillä yksilöhaastatteluilla. Valitut haastateltavat ovat kokeneita etätyöntekijöitä eri aloilta, jotka toimivat kansainvälisissä yrityksissä, ja ovat vähintään työskennelleet vuoden etätyössä. Tutkimuksen löydöksiä tarkastellaan kansainvälisen liiketoiminnan näkökulmasta, pyrkien vastaamaan siihen, mitä yritysjohto voi tästä oppia. Tulokset osoittavat etätyöntekijöiden olevan itsenäisiä, sisäisesti motivoituneita että myös päteviä oman alansa asiantuntijoita. Etätyön suuret edut korostuvat sen joustavassa luonteessa sekä monissa käytännön hyödyissä, joita etätyö tarjoaa. Näistä esimerkkeinä toimivat muun muassa vapaa-ajan laadun parantuminen sekä erinäiset taloudelliset hyödyt. Etätyön suuria heikkouksia yksilön ja organisaation näkökulmasta luo sosiaalisen yhteenkuuluvuuden tunteen puute. Etenkin epävirallisen kommunikaation vähentyminen luo kuilun yksilöiden ja organisaatioiden välille. Tämä aiheuttaa haasteita yrityskulttuurin rakentamisessa ja haastaa etätyöntekijöiden kokemusta työnsä merkityksellisyydestä. Etätyöntekijöiden tuottavuus verrattuna toimistossa työskenteleviin työntekijöihin havaitaan joko kasvavan tai pysyvän yhtä suurena tämän tutkimuksen perusteella. Erityinen huomio aikaisempaan tutkimukseen verrattuna tulee etätyön aikaisemminkin todettujen hyötyjen kytkeytymisestä pragmaattisiin käytännön seikkoihin, kuten stressin vähentymisen liittyen esimerkiksi pukukoodin puuttumiseen. Tämän tutkimuksen johtopäätökset korostavat tarvetta tukea etätyöntekijöiden autonomiaa ja vapautta sekä toteuttamaan ratkaisuja, jotka eivät ainoastaan koita matkia fyysisesti tapahtuvaa viestintää, vaan nostavat etätyön tasavertaiseksi paikallisesti tapahtuvan kommunikaation rinnalle hyödyntämällä esimerkiksi virtuaalitodellisuutta tai yhteistyöskentelytiloja.
Keywords: international business, remote work, self-determination, digital work, motivation, kansainvälinen liiketoiminta, etätyö, itseohjautuvuus, digitaalinen työ, motivaatio